MODERN APPROACHES TO TEACHING THE MOYHER TONGUE AND FOREIGN LANGUAGES AND ISSUES OF INTERCULTURAL COMMUNICATION - Mahmudova Munisaxon Foziljon qizi; Ruzmetova Diana Komilovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
ABSTRACT This article explores contemporary methods used in teaching both the mother tongue  and  foreign  languages,  with  a  particular  focus  on  how  intercultural communication is integrated into modern educational practices. It analyzes innovative pedagogical approaches, communicative strategies, digital tools, and the significance of cultural awareness in developing language competence.